Social Capital and Educational Attainment: A Study of Undergraduates in a Faculty of Education - Etcheverry, Emily; Clifton, Rodney A.; Roberts, Lance W. (Alberta Journal of Educational Research, 2001)
This research examines the effects of social capital on the development of knowledge, skills, and attitudes among a sample of undergraduate university students. A theoretical model containing 14 variables including university and social background, social capital, time management, and educational attainment is presented. The data obtained from questionnaires completed by 269 undergraduate students in the Faculty of Education at a western Canadian university are used to test the model. Structural equation modeling tests the relationships among the variables. The results indicate that when other variables are taken into account, students' perceptions of social capital resources have direct and indirect effects on their developing self-concepts and their educational achievement. Students' perceptions of support, specifically support derived from interactions with other students, are an important resource that relates positively to their academic self-concepts and their grades.